Improvement of Pennisetum purpureum in Cuba - Herrera, Rafael Segundo (Cuban Journal of Agricultural Science, 2009)
At the middle of the 80?s in the Institute of Animal Science, it started a program of improvement of Pennisetum purpureum through the use of biotechnology (in vitro tissue culture) and mutagenesis (radiation with 60Co). This responded to, at that time, the most spread and used Pennisetum varaiety was King grass, which occupied 85 % of the forage areas in the country. The object of this program was the obtainment of new varieties with superior traits and that responded favorably to adverse conditions such as salinity and drought. Several clones were obtained through in vitro tissue culture. Out of them, two were selected: Cuba CT-115 and Cuba CT-169. The former was used to developed the biomass bank technology for grazing and to fulfill the feed deficit in the dry season, whereas the latter is purely for forage. Through mutagenesis, two new clones were obtained Cuba MF-24 and Cuba MQ-1 which by being exploited in dry conditions and with moderate doses of nitrogenous fertilizer, surpass the yields of king grass. Also, others were obtained having better agronomic and quality indicators. Special care was paid to drought and salinity, and the clones managed to surpass the yields of their predecessors. It was concluded that plants were obtained having favorable traits for forage production, grazing, drought and salinity resistance, as well as with better agronomic and quality indicators. Further studies are suggested using fertilization strategically and introducing new plants in commercial production, having wide variety of germplasm for further studies. Key words: improvement, Pennisetum purpureum.